Redefining radio: Implications for journalism education in an era of digital audio storytelling. (1st October 2016) - Wake, Alexandra; Bahfen, Nasya
This article seeks to map the current position of audio within journalism curriculums at Australian and New Zealand universities, in the context of a so-called renaissance in podcasting helping to lift the profile of audio among educators and industry. Internet radio and podcasting have grown exponentially since 2004, with the worldwide monthly audience for podcasts estimated at more than 35 million listeners (Markman and Sawyer 2014). Podcasts are offered by traditional broadcast organisations, online newspapers, and non-media organisations or individuals. Yet while digital content production may have changed the competitive industry in which journalism graduates seek employment, journalism education has yet to react to that change in a comprehensive manner (Carey 2000; Hirst and Treadwell 2011). There is an acknowledged lack of research on long-form audio journalism (McHugh 2014; Panda 2014) but there is also little recent research on how journalism programs in universities are meeting this new audio demand.